Strengthening Islamic Environmental Awareness through Exploring Poetry as a Learning Resource in Social Studies - Mutiani Mutiani; Rusma Noortyani; Tetep Tetep; Jumriani Jumriani; Triani Widyanti (Islam Realitas: Journal of Islamic and Social Studies, 2020)
This article aims to describe how an anthropocentric perspective can lead to an ethical solution to resolving the ecological crisis. The ecological crisis should be seen as a misrepresentation of the role of human beings in exceeding the limits of environmental exploitation as mandated in Islam. Therefore, education should be used in offering solutions and innovations in the various scholarly disciplines, such as social studies. One innovation is the use of poetry as a learning resource for social studies. Poetry exploration is devoted to utilizing the value of local poetry. A qualitative approach is used to describe a value-based social studies learning concept. This study focuses on the poem of Huma Yang Perih, which describes agricultural conditions in South Kalimantan that have begun to be abandoned by farmers. Even though the poem was published in 1978, this condition has persisted to this day. Through Huma Yang Perih, it is hoped that we can reflect on the importance of human continuity at all times, so that humanity no longer underestimate the changing lifestyles rural people and their migration to cities. Artikel ini bertujuan mendeskripsikan pandangan antroposentrisme sebagai cara etis untuk menuntaskan krisis ekologi. Krisis ekologi, patut dipandang sebagai bentuk kesalahan peran manusia dalam melampaui batas eskploitasi lingkungan sebagaimana diamanatkan dalam Islam. Oleh karena itu, diperlukan ruang edukasi sebagai satu solusi dan inovasi di bidang pembelajaran, seperti IPS. Satu inovasi yang dimaksudkan adalah pemanfaatan puisi sebagai sumber belajar IPS. Eksplorasi puisi dikhususkan dengan pemanfaatan nilai dari puisi lokal. Pendekatan kualitatif digunakan untuk mendeskripsikan makna yang relevan dengan konsep pembelajaran IPS berbasis nilai. Hasil penelitian menjelaskan puisi Huma Yang Perih yang menggambarkan kondisi pertanian di Kalimantan Selatan yang sudah mulai ditinggalkan petani. Meski puisi tersebut terbit tahun 1978, kondisi tersebut tetap bertahan hingga saat ini. Melalui Huma Yang Perih, diharapkan kita bisa merefleksikan betapa pentingnya kesinambungan manusia setiap saat. Sehingga masyarakat tidak lagi menganggap remeh untuk mengubah gaya hidup pedesaan dan bermigrasi ke perkotaan